LGBT DALAM TAKARAN SOSIOLOGI HUKUM - Musa Arifin (Institut agama islam negeri Padangsidimpuan, 2016)
One of current controversial phenomenon which many people talk about in the society is the legalation of lesbian, gay, bisexual and transgender (LGBT) from government. The assertion from LGBT community comes along with bigger population growth of LGBT communities. The declaration done by these communities directed to be national attention by publicating with some big electronic media.